Improvement of African rice (O. glaberrima) collection to enhance its nutritional profile - CGIAR Research Program on Rice (2019)
Thirteen rice varieties exhibiting weak digestive properties following parboiling have been identified and 1021 lines from the AfricaRice Rice Biodiversity Center for Africa have been analyzed for grain physical quality, aroma, amylose and protein content. Results showed that digestive properties were influenced by resistant starch, total starch and protein contents.